2016
DOI: 10.1155/2016/4357656
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity Effects of Unripe Rubus coreanus Miquel and Its Constituents: An In Vitro and In Vivo Characterization of the Underlying Mechanism

Abstract: Background. The objective of the present study was to perform a bioguided fractionation of unripe Rubus coreanus Miquel (uRC) and evaluate the lipid accumulation system involvement in its antiobesity activity as well as study the uRC mechanism of action. Results. After the fractionation, the BuOH fraction of uRC (uRCB) was the most active fraction, suppressing the differentiation of 3T3-L1 adipocytes in a dose-dependent manner. Moreover, after an oral administration for 8 weeks in HFD-induced obese mice, uRCB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 43 publications
4
35
0
1
Order By: Relevance
“…We did not examine, however, why the lipid profile was improved by KH-204 treatment. Although some reports have described the antiobesity and hypolipidemic effects of Lycium chinense Miller and Rubus coreanus Miquel [ 24 , 25 ], there is little scholarly evidence available that would explain the improvement in lipid profile seen in our study. Thus, further study should be conducted to elucidate the hypolipidemic mechanisms of this formula.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We did not examine, however, why the lipid profile was improved by KH-204 treatment. Although some reports have described the antiobesity and hypolipidemic effects of Lycium chinense Miller and Rubus coreanus Miquel [ 24 , 25 ], there is little scholarly evidence available that would explain the improvement in lipid profile seen in our study. Thus, further study should be conducted to elucidate the hypolipidemic mechanisms of this formula.…”
Section: Discussionmentioning
confidence: 67%
“…et Zucc, Lycium chinense Miller, Rubus coreanus Miquel, Cuscuta chinensis Lam, and Schisandra chinensis Baillon. Several studies have reported that each herb or various combinations of these herbs have a number of beneficial properties, including antioxidant [ 13 18 ], anti-inflammatory [ 15 , 19 ], anti-apoptotic [ 17 , 20 , 21 ], anti-fibrotic [ 15 , 22 , 23 ], and hypolipidemic effects [ 24 , 25 ] in multiple diseases. These herbs have been widely used in Korea as medicines for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Unripe R. coreanus is a functional food or nutraceutical supplement that is useful for the prevention of noncommunicable diseases, especially cardiovascular diseases (CVDs). We previously reported the effects of a 5% ethanol extract of unripe R. coreanus (5-uRCK) on CVD-related diseases such as hyperlipidemia and obesity [3][4][5][6]. The effects of this extract may reduce the risk for CVDs, including hypertension, atherosclerosis, stroke and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is caused by imbalances in energy intake and energy expenditure, and excessive energy tends to form triacylglycerols that accumulate in cells to make cell hypertrophy (Fruhbeck et al, 2001). PPARγ and C/EBPα can activate ACC and FAS to increase the efficiency of lipid synthesis (Oh et al, 2016). The results showed that WEPE can reduce the protein expressions of PPARγ and C/EBPα (Figure 5b), and thus inhibit the p-ACC and FAS proteins (Figure 5c) to reduce fat accumulation in adipocytes.…”
Section: Wepe Allays Mg-induced Insulin Resistancementioning
confidence: 99%